Perempuan dan Agensi: Analisis Feminisme Poskolonial atas Pekerja Seks Perempuan di Danau Tempe (JURNAL DURA NEGARA, 2026)
This research aims to explore how the sexualities of female sex workers (PSP) in the Danau Tempe area of Sanur, Bali, are constructed, negotiated, and utilized as strategies for survival in the unequal social and economic structures. Using a qualitative research design with purposive sampling, in-depth interviews were conducted with female sex workers in the Danau Tempe area who have been operating in the commercial sex industry for over ten years. The data were analyzed using descriptive qualitative analysis to interpret empirical findings within the social-cultural context. The study reveals that women’s decisions to remain in sex work cannot be reduced to economic hardship alone, but it shows how structural pressure, economic marginalization, social exclusion, and the intertwining with personal agency are shaping their choices. Participants conceptualize sex work as a means of achieving economic autonomy and resisting dominant patriarchal norms. This research offers a postcolonial feminist perspective that challenges Western universalism about prostitution in third-world countries and recognizes sex work as a form of labor embedded within broader power relations.